The Impact of Covid-19 Pandemic to the Construction Industry in Malaysia - YUGASHINI RAJENDRAN,; Muhammad Fikri Bin Hasmori , (Recent Trends in Civil Engineering and Built Environment, 2022)
The World Health Organization (WHO) declared the Covid-19 outbreak as a pandemic and it effect the construction industry due limitation in movement of people. Hence, this research was conducted to identify the impact of Covid-19 pandemic and to measure the effects of Covid-19 pandemic accordingly to the level of severity at Wilayah Perseketuan Kuala Lumpur, Peninsular Malaysia. Data collection was based on online questionnaires through google form and the findings were analyzed by descriptive statistics and Relative Importance Index (RII) method. Based on the result, resources deficiency, field work, project management and financial impact are the impacts of Covid-19 pandemic in the construction industry. Based on the relative importance index, cost overruns, restriction of movement at construction site, facing supply shortage of material, delays in preparation of drawings and materials samples and financial market instability are the main impacts in the construction industry and this help project stakeholders to realize the sequences of the sudden epidemic.